FIGO-staging of cervical cancer: Can’t it be communicated in a better way? - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aim: To correlate existing format of FIGO-staging of cervical cancer in clinical practice. Method: Review of clinical practice guidelines and journal publications. Result of clinical practice guidelines. Conclusion: A modified form of cervical cancer staging is proposed to make it practical for clinical evaluation, provisional management plan and prognosis based on tumor size and parametrial invasion. DOI: http://dx.doi.org/10.3126/njog.v3i2.10837 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 62-65